A robust control scheme for nonlinear non-isothermal uncertain jacketed continuous stirred tank reactor. (March 2017) - Wallam, Fahad; Memon, Attaullah Y.
Highlights: Novel Integral Sliding Mode Control (ISMC) is proposed for Jacketed Non-isothermal Continuous Stirred Tank Reactor (CSTR). Robust performance comparison among the proposed ISMC, conventional ISMC and Super Twisted Algorithm SMC is presented. High Gain Observer (HGO) and Extended High Gain Observer (EHGO) are also proposed for the CSTR process. Comparison of robust capabilities of HGO and EHGO is presented. EHGO and the proposed ISMC based output feedback scheme is also evaluated for robustness and reference tracking capabilities, Abstract: A Non-isothermal Jacketed Continuous Stirred Tank Reactor (CSTR) is extensively used in chemical as well as in other process industries to manufacture different products. The dynamics of non-isothermal CSTR are highly nonlinear and open-loop unstable in nature. Moreover, it may have parametric uncertainties, disturbances and un-modeled side reactions which may cause the reactor temperature to deviate from the reference value. This deviation may degrade quality of the product because the chemical reaction inside the CSTR depends on reactor temperature. For such a nonlinear, unstable and uncertain process, designing a control scheme with the ability to reject the effects of disturbances along with a good reference tracking capability is a challenging control engineering problem. In this work, a novel robust sliding mode control technique named as Improved Integral Sliding Mode Control (IISMC) has been presented for uncertain non-isothermal jacketed CSTR process. Moreover, a variety of recently developed sliding mode control techniques such as Classical Integral Sliding Mode Control (CISMC) and Super Twisted Algorithm based Sliding Mode Control (STA-SMC) have also been devised and compared with the proposed approach in order to investigate the effectiveness of the proposed scheme. A Lyapunov based analysis has also been provided to assure the robust stability of the closed loop process. Furthermore, in order to extend the state feedback approach to the output feedback scheme, two robust observers; High Gain Observer (HGO) and Extended High Gain Observer (EHGO), are also designed for the very process. They have also been compared with each other and have been investigated for robust stability using Lyapunov based approach. Finally, an output feedback control scheme using IISMC and EHGO has been presented and its performance has been examined and compared with the IISMC based state feedback approach. The simulation results show that the proposed control scheme effectively rejects the uncertainties and disturbances without leading the process to instability and offers good reference tracking capabilities.